"Is There Toleration in Islam?" Reframing a Post-Islamist Question in a Post-Secular Context. (1st October 2016) - Mohammad Mahdi Mojahedi
Abstract : This article presents a critical appraisal of the post-Islamist position in the discourse on toleration in Islam. It starts with a critical overview of post-Islamism and its position on pluralism and toleration. Contextualising the post-Islamist discourse on toleration in the broader context of post-secular critique of modernity and theoretical debates on pluralist toleration, as opposed to monist (or hegemonic) toleration, post-Islamism will be criticised here for its missing the pluralist point of toleration, consequently confusing it with monist and hegemonic toleration, as well as its extreme submission to culturalism in understanding the dynamics of political transformation, and its unconditional confidence in "the secularization thesis" or "the secularization theory."